Korelasi Integritas Akhlak Pelaku Ekonomi dengan Kesuksesan Bisnis - Damanhuri; Misbah, T. Lembong; Hasyim, Syarifuddin; Mistiar , Wolly (Yayasan Kawanad, 2023)
This research explores in depth the concept of moral integrity which is the main basis for economic actors in the current context. The focus of this research is to identify ethical principles that should be upheld and behaviors that economic actors should avoid ensuring sustainability and fairness in economic interactions. A qualitative approach is used to investigate the impact of moral integrity on economic decisions. Research findings show that moral integrity must involve a commitment to values such as honesty, justice, and social responsibility. On the other hand, behavior that should be avoided includes practices that can harm society, such as fraud, corruption, and exploitation. This article provides a holistic picture of the role of moral integrity in shaping the character of economic actors and its impact on economic sustainability. The implications of this research finding can guide companies, regulators, and individuals in designing policies, business practices, and ethical guidelines that are in accordance with Islamic moral and justice principles. This research contributes to a deep understanding of moral integrity in the complex context of today's economic interactions.